(untitled) (Research, Society and Development, 2020)
The present work was developed with the objective of exposing the relationship between mathematics used in students’ daily lives and mathematics taught at school, relating contextualized mathematical problems with everyday life. So that, in this way, students improve their knowledge and have more interest in mathematics classes, resulting in effective learning. The research was carried out at the State School located in the city of Cajazeirinhas-PB, with high school students. It was based on the survey test, which was given a questionnaire to the class teacher and another one for the students. The research is characterized as qualitative research in the action research modality. In view of the results obtained, it can be seen that some students are unable to relate mathematics to their daily lives and professions, making it necessary for teachers to seek to understand the needs that students have in the teaching of mathematics, always showing each content addressed, the importance and relationship that mathematics has in their daily lives, making it possible for students to acquire interest in the discipline.